An Exploration of Non-Coding RNAs in Extracellular Vesicles Delivered by Swine Anterior Pituitary - Jiali Xiong (Frontiers Media S.A., 2021)
Extracellular vesicles are lipid bilayer-delimited particles carrying proteins, lipids, and small RNAs. Previous studies have demonstrated that they had regulatory functions both physiologically and pathologically. However, information remains inadequate on extracellular vesicles from the anterior pituitary, a key endocrine organ in animals and humans. In this study, we separated and identified extracellular vesicles from the anterior pituitary of the Duroc swine model. Total RNA was extracted and RNA-seq was performed, followed by a comprehensive analysis of miRNAs, lncRNAs, and circRNAs. Resultantly, we obtained 416 miRNAs, 16,232 lncRNAs, and 495 circRNAs. Furthermore, GO and KEGG enrichment analysis showed that the ncRNAs in extracellular vesicles may participate in regulating intracellular signal transduction, cellular component organization or biogenesis, small molecule binding, and transferase activity. The cross-talk between them also suggested that they may play an important role in the signaling process and biological regulation. This is the first report of ncRNA data in the anterior pituitary extracellular vesicles from the duroc swine breed, which is a fundamental resource for exploring detailed functions of extracellular vesicles from the anterior pituitary.